KINERJA KOMITE SEKOLAH PADA PROGRAM PENDIDIKAN GRATIS DI SMP NEGERI 1 POLOKARTO KABUPATEN SUKOHARJO - Suyadi, Agus (2011)
This study aims to (1) Describe the characteristics of the role of the organizational structure of the school committe on Junior High School 1 Polokarto Sukoharjo district. (2) Describe the characteristics of institutions working with other school principals on Junior High School 1 Polokarto Sukoharjo district. (3) Describe the characteristics of the work values of school committes on Junior High School 1 Polokarto Sukoharjo district. Research carried out on Junior High School 1 Polokarto Sukoharjo, the research is a qualitative study. To obtain the data used in the study of documentary methods (as the principal method), observational methods, interview methods (interview). The data analysis technique in this research using descriptive techniques with three procedures, namely: (1) data reduction, (2) presentation of data, and (3) conclusion verification. The results are (1) Characteristics of organizational structure the role of school committes on Junior High School 1 Polokarto Sukoharjo district in the form of organizational role of the school committe as the principal partners in planning, implementing, evaluating school activities, in terms of educational planning role of the school committe to give false advice in the preparation Program and Budget Plan for Schools (School Budget) School Committe has submitted a role or to provide an aid or similar ideas in the context of compiler RKS and budgets. (2) The network is working with the school's head teacher institute especially in terms of planning the conduct of learning is done in the form of clinical supervision, and guidance in curriculum development. Hubugan cooperation with other school principals conducted by the school principal through an open and harmonious communication, in a formal atmosphere mauplun informal, both during and outside office hours office hours. (3) The school committe in the planning work in the form of brainstorming in the preparation of RKS and budgets. Value of construction work in the physical form of filing false financial advice and support for physical development. Value of work in learning evaluation is realized in the form of prayer support. Value of work in improving facilities and infrastructure is realized in the form of support to sekolah.Nilai working in the financial responsibility, especially funds that are not listed in the budgets, is to participate dana.Nilai use policies account for its work in the financial responsibility set forth in detail in budgets, school committe aware of any expenditures made by school